The electroconductivity of the liquid alloys of transition metals - Shvets, V.T.; Savenko, S.V.; Datsko, S.V. (Condensed Matter Physics, 2004)
The concentration dependance of electroresistivity of the liquid binary alloys of transition metals Fe, Co and Ni is calculated. We considered the contribution to conductivity from the s-electrons, described within the model of nearly free electrons. The role of the partially occupied d-bands is reduced to resonance scattering of the s-electrons on d-states. The interaction of the s- and d-electrons is described by the hybridization potential of s- and d-states. The interaction with the ions, not including the partially occupied d-states, is described using the pseudopotential of the electronion interaction. The electroresistivity of the alloys is calculated in the second order of the perturbation theory in pseudopotential and hybridization potential. The concentration dependance of electroresistivity of the binary alloys approaches the linear regime as the resonance scattering of the s-electrons on d-states prevails over the scattering on the ions. The calculations exhibit good agreement with the experimental data.